Identification and persistence mechanism of very small glaciers and perennial snow patches in the northern Japanese Alps - Arie, Kenshiro; Narama, Chiyuki; Fukui, Kotaro; Iida, Hajime (Frontiers in Earth Science, 2025)
In this study, we measure ice thickness and flow and reveal that Shakushizawa and Kaerazuzawa perennial snow patches (PSPs) in the northern Japanese Alps are glaciers instead. Due to their size, they are very small glaciers (VSGs). For the Shakushizawa VSG investigated by this study, we also calculate the long-term average annual surface mass balances to assess the persistence mechanisms of VSGs in this region. The mass balance calculation is done by substituting the ice thickness and surface flow velocity measured on the Shakushizawa VSG into the continuity equation under the assumption of the steady-state in the long-term average. The annual surface mass balance altitude profile in the long-term average of the Shakushizawa VSG has a positive gradient with the accumulation area upstream and the ablation area downstream. If the other VSGs in the northern Japanese Alps have the same characteristics, these have a localized accumulation area in the long-term average below the climatic ELA by topographic effects. These results suggest that glaciers in the northern Japanese Alps are maintained due to topographic effects, despite being located below the climatic equilibrium line altitude (ELA).